Ovarian Structure and Oogenesis of Loliolus (Loliolus) affinis Steenstrup, 1856 from Estuarine Pranburi River, Thailand - รอดเรืองศรี ศุภลักษณ์; กำเนิดนิล ทัตพล; ทองบุญ ละม้าย; เสนารัตน์ ศิลปชัย; พูลประเสริฐ พิสิษฐ์; เกษตระทัต เจษฏ์; จิรอังกูรสกุล วรรณีย์; ภารา ชำนาญ (YRU Journal of Science and Technology, 2018)
Most of the histological studies on squid ovary have been conducted and widely disseminated in foreign countries. When compared with Thailand, these similar studies are underresearched. This current study was thus performed on the structure of the ovarian maturation and oogenesis of Loliolus (Loliolus) affinis Steenstrup, 1856 from Estuarine Pranburi River, Thailand, using histology and histochemical techniques before a further investigation on the reproductive cycle and histopathology in the future. The results revealed that L. (Loliolus) affinis ovary was an asynchronous-type ovary and the ovarian parenchyma contained oocytes at various stages of development. When viewed under light microscopy, the ovarian structure was enclosed by a thin of tunica albuginea. The oogenesis of this squid could then be divided into eight developmental stages including oocyte stage 1, oocyte stage 2, oocyte stage 3, oocyte stage 4, oocyte stage 5, oocyte stage 6, oocyte stage 7 and oocyte stage 8. These features were similarly found in other squids studied by previous studies.